UNVEILING THE CHALLENGES FACED BY NON-PROFIT ORGANISATION IN MALAYSIA - Nur Hayati Ab Samad; Noor Hazlina Ahmad (International Journal of Accounting, Finance and Business, 2021)
Non-profit organisations (NPOs) play significant roles in social service delivery and other aspects of sustainable development. In order to continuously fulfil the organisational mission, the NPOs must address challenges that may hamper NPOs sustainability. Hence, this study aimed to identify the challenges faced by NPOs to remain sustained. Through a semi-structured interview with NPOs in Malaysia, five main challenges outlined. NPOs faced difficulties in term of lack of fund, lack of human capital and facilities, lack of cooperation and support from stakeholders, lack of trust, and misalignment of interest between NPO and stakeholders. This study’s findings contribute to the literature of non-profit by highlighting the challenges faced by NPOs to remain sustained. This study’s findings help NPOs, and relevant regulators plan for the potential remedy or strategies to tackle the identified challenges.